The Effectiveness of Multimedia-Based Interactive Learning Media on Mathematics Learning Outcomes in 7th Grade Students - Baharuddin Abbas (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2021)
This study aims to determine the effectiveness of multimedia-based interactive learning media on mathematics learning outcomes. This research is a quantitative type of experiment with Pre-Experimental Design. The research design used is the One-Group Pretest & Posttest Design, which is an experiment which is carried out in one group only without a comparison group. The population in this study were all students of class VII MTs Madani Alauddin Pao-pao Kab. Gowa, amounting to 220 people. The sample in this study was class VIIA totaling 37 people. In this study, there are two variables, namely: (1) Variable X: Multimedia-Based Interactive Learning Media. (2) Variable Y: Mathematics Learning Outcomes. The data collection techniques used in this study are: learning outcome tests consisting of pre-test and post-test as well as observation sheets for the implementation of the learning process. The research hypothesis test in this study is to use paired sample t-test. The pre-test values are mean of 49.7295; standard deviation of 15.91604. The value ranges from 13.33 to 80.00. The Post-Test Value is the Mean of 71.3514; standard deviation of 14.72978. Value ranges from 40.00 to 100.00. Because the mean value of the pre-test learning outcomes was 49.7295 <71.3514, then descriptively there was a difference in the average learning outcomes between the pretest and the post-test results. Based on the paired sample t test, it is known that the sig. (2-tailed) value is 0.000 <0.05. So it can be concluded that there are differences in the average student learning outcomes before the application of multimedia-based interactive learning media